The complex HLA-E-nonapeptide in Behçet disease - Castaño-Núñez, Ángel Luís; Montes-Cano, Marco-Antonio; García-Lozano, José-Raúl; Ortego-Centeno, Norberto; García-Hernández, Francisco José; Espinosa, Gerard; Graña-Gil, Genaro; Sánchez-Bursón, Juan; Juliá, María Rosa; Solans, Roser; Blanco, Ricardo; Barnosi-Marín, Ana-Celia; et al. (Frontiers in Immunology, 2023)
The knowledge of the aetiology of Behçet disease (BD), an immune-mediated vasculitis, is limited. HLA-B, mainly HLA-B51, and HLA-A molecules are associated with disease, but the ultimate cause of this association remains obscure. There is evidence that NK cells participate in the etiopathology of BD. NK cells have activator and inhibitor surface receptors, like the KIR and the NKG2 families. Classical HLA-class I molecules (A, B and C) are keys in the activity control of the NK because they are KIR ligands. Most NKG2 receptors bind HLA-E, which presents only nonapeptides derived from the signal peptide of other class-I molecules. This study investigates the contribution of the pair HLA-E and ligand, nonapeptide derived from the 3-11 sequence of the signal peptides of class I classical molecules, to the susceptibility to BD. We analyzed the frequency of the HLA-derivated nonapeptide forms in 466 BD patients and 444 controls and an HLA-E functional dimorphism in a subgroup of patients and controls. In B51 negative patients, the frequency of VMAPRTLLL was lower (70.4% versus 80.0% in controls; P=0.006, Pc=0.04, OR=0.60, 95%CI 0.41-0.86), and the frequency of VMAPRTLVL was higher (81.6% versus 71.4% in controls; P=0.004, Pc=0.03, OR=1.78, 95%CI 1.20-2.63). In homozygosity, VMAPRTLLL is protective, and VMAPRTLVL confers risk. The heterozygous condition is neutral. There were no significant differences in the distribution of the HLA-E dimorphism. Our results explain the association of BD with diverse HLA-A molecules, reinforce the hypothesis of the involvement of the NK cells in the disease and do not suggest a significant contribution of the HLA-E polymorphism to disease susceptibility.